Industrial assessment to technical and employability skills students based on KKNI (in Jakarta Region) - Rina Febriana; Agung Premono; Tuti Iriani (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
This study aims to determine the industrial assessment of technical and employability skills of students. The research was conducted by using survey method in several industries as the place of the Job Training (PKL) of the students. The research technique used purposive random sampling with respondents in this research consist of 23 industry in Jakarta area. The results of the research are (1) the industrial assessment of the technical skills of the students obtained a score of 73.10 with high interpretation; (2) The industry average rating of employability of students skills is 83.10 with very high interpretation.